Study on the Migration Law of Overlying Strata on the Working Surface of Large Mining Height in Y.C.W Coal Mine. (25th April 2022) - Liu, Hongtao; Huo, Tianhong; Liu, Yang; Han, Zhou; Han, Zijun; Liang, Wanliang
Abstract : The migration law of overlying strata on working face is of great significance for safe mining of working face. In this paper, theoretical calculation, numerical simulation, and similar simulation are used to study the distribution characteristics, migration, and fracture law of key strata in the overlying strata of 130204 working face of Y.C.W coal mine and the relationship between the development height of water flowing fractured zone and the spatial position of weak aquifer. The theoretical calculation results show that there are "one main two sub" key strata in the overlying strata of 130204 working face, which play an important role in controlling rock movement. Numerical simulation and similar simulation results show that the first weighting step distance of the direct roof of 130204 working face is about 30-40 m. The initial weighting interval of the basic roof of the working face is about 70-80 m, and the periodic weighting interval is about 23.5-25 m. After the first weighting and multiple periodic weighting of the basic roof of the working face, the first subcritical layer is located in the caving zone, the second subcritical layer is located in the fracture zone, and the main key layer is finally located in the bending subsidence zone. The final height of the caving zone of the overlying strata is about 24 m, and the height of the water flowing fractured zone is about 130 m. Since the water-conducting fractured zone is connected and passes through the second subcritical layer with weak water-bearing property, it is possible for the water permeability accident of the working face. Therefore, in order to ensure the safety of the working face, the water should be detected and released in advance during the mining of the working face.